Systemic Inflammation, Oxidative Damage to Nucleic Acids, and Metabolic Syndrome in the Pathogenesis of Psoriasis - Borska, Lenka; Kremlacek, Jan; Andrys, Ctirad; Krejsek, Jan; Hamakova, Kvetoslava; Borsky, Pavel; Palicka, Vladimir; Rehacek, Vit; Malkova, Andrea; Fiala, Zdenek (International journal of molecular sciences, 2017)
In the pathogenesis of psoriasis, systemic inflammation and oxidative stress play mutual roles interrelated with metabolic syndrome (MetS). This study aims to map the selected markers of inflammation (C-reactive protein (CRP)), oxidative damage to nucleic acids (DNA/RNA damage; 8-hydroxy-2'-deoxyguanosine, 8-hydroxyguanosine, and 8-hydroxyguanine), and the parameters of MetS (waist circumference, fasting glucose, triglycerides, high-density lipoprotein (HDL) cholesterol, diastolic and systolic blood pressure) in a group of 37 patients with psoriasis (62% of MetS) and in 43 healthy controls (42% of MetS). Levels of CRP, DNA/RNA damage, fasting glucose, and triglycerides were significantly elevated in patients. MetS in conjunction with psoriasis was associated with high levels of CRP, significantly higher than in control subjects without MetS. Patients with MetS exhibited further DNA/RNA damage, which was significantly higher in comparison with the control group. Our study supports the independent role of psoriasis and MetS in the increase of CRP and DNA/RNA damage. The psoriasis contributes to an increase in the levels of both effects more significantly than MetS. The psoriasis also diminished the relationship between CRP and oxidative damage to nucleic acids existent in controls.
Keywords: psoriasis; oxidační stres; poškození DNA; Male; Inflammation; DNA Damage; psoriáza; oxidative stress; mužské pohlaví; metabolický syndrom; zánět; Metabolic Syndrome; lidé; Psoriasis; ženské pohlaví; Humans; inflammation; Female; Oxidative Stress; metabolic syndrome; lidé středního věku; Middle Aged